662 Navigation in Cervical Spine Surgery: A Review of Past and Current Uses. (April 2023) - Avila, Mauricio J.; Farhadi, Dara; Cavagnaro, María José; Orenday, Jose; Fellow, Research; Hussein, Amna; Reyes, Angelica Alvarez; Bauer, Isabel; Khan, Naushaba; Strouse, Isabel Martha; Baaj, Ali A.
Abstract : INTRODUCTION: The last two decades in spine surgery have resulted in an expansion of innovation and new enabling technologies. Within those new developments, spinal navigation has been adopted widely. Nonetheless, the use in the cervical spine remains a less explored METHODS: A scoping review of the literature was performed via PubMed. Limited to English and no date limit. Different search queries with MesH terms such as "Surgical Navigation Systems" "Spatial Navigation", "Surgery, Computer-Assisted", "Cervical Vertebrae", "cervical spine" with combination of OR and AND. Inclusion criteria: articles discussing the use of any navigation platform in the cervical spine. RESULTS: A total of 365 articles were found. After title and abstract selection, a total of 87 articles were reviewed. All the articles were retrospective. A total of 2101 patients underwent cervical procedures with spinal navigation, 54% were male. Average age of the cohort was 53.6 years. The Stealth navigation system (Medtronic) was the most commonly used followed by BrainLab and the large majority used CT based navigation. Degenerative conditions were the most common followed by trauma. There were 1872 total screws placed under navigation. Most common use for navigation was placement of cervical pedicle screws with a range of pedicle screw accuracy from 76.5-97.1%. The most common level for misplacement was C4. Additional uses include occipital and C1-2 fusion, corpectomies, transoral, transnasal approaches, and tumor localization. Direct complications from screw placement: C5 palsy, vertebral artery injury and dural tears. Mean follow up was 22.6 months. CONCLUSIONS: Spinal navigation in the cervical spine remains an understudied field. The current reports show good accuracy for placement of cervical pedicle screws, with minimal complications but other uses within the cervical spine remain somewhat limited. Given our evolving understanding of cervical pathology